2024
DOI: 10.3389/fonc.2024.1334156
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT imaging in pulmonary sarcomatoid carcinoma

Zhe-Huang Luo,
Xiao-Yan Luo,
Wan-Ling Qi
et al.

Abstract: BackgroundPulmonary sarcomatoid carcinoma (PSC) is a rare highly aggressive and poorly differentiated non-small cell carcinoma, and little is known about the information on the usefulness of 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT). We investigated the clinical and 18F-FDG PET/CT features of PSC.MethodsWe retrospectively analyzed 25 consecutive PSC patients who had undergone 18F-FDG PET/CT. Demographic data, PET/CT findings before treatment, pathological featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In our case, PET/CT identi ed a newly discovered left adrenal nodule, which exhibited high FDG uptake (SUVmax 5.7), compared to what was observed on enhanced CT. At present, there is no research report on PET/CT imaging features of the small intestine SCA. Previous studies have reported that primary pulmonary SCA tumours exhibit abnormal uptake of 18 F-FDG, with maximum standardized uptake values (SUVmax) ranging from 4.1 to 35.5 (Luo et al 2024); the SUVmax of these lesions is often higher than that observed in other types of non-small cell lung cancer (NSCLC).…”
Section: Ct Scan Imaging and Molecule Imagingmentioning
confidence: 99%
“…In our case, PET/CT identi ed a newly discovered left adrenal nodule, which exhibited high FDG uptake (SUVmax 5.7), compared to what was observed on enhanced CT. At present, there is no research report on PET/CT imaging features of the small intestine SCA. Previous studies have reported that primary pulmonary SCA tumours exhibit abnormal uptake of 18 F-FDG, with maximum standardized uptake values (SUVmax) ranging from 4.1 to 35.5 (Luo et al 2024); the SUVmax of these lesions is often higher than that observed in other types of non-small cell lung cancer (NSCLC).…”
Section: Ct Scan Imaging and Molecule Imagingmentioning
confidence: 99%